The Lecturers’ Perception of the Implementation of Content-Based Instruction in Teaching English for Hospitality - Kartini; Sulaiman, Iskandar; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2025)
The main purpose of this study is to explore the lecturers’ perceptions on the implementation of Content-Based Instruction (CBI) in teaching English for hospitality at Poltekpar Makassar. Using a qualitative case study design, data were collected through semi-structured interviews with two lecturers and eight students. The results show that the respondents consider CBI as an effective pedagogical strategy, which intertwines language learning with content and makes English instruction more meaningful and transferrable in their future professions within the hospitality industry. CBI also improves language skills along with content knowledge by integrating language instruction into subjects like cooking, customer service and tourism. This method, by engaging students in real-world tasks and practical assignments, fosters contextualized learning, enhances student involvement, and stimulates critical and communicative competence in the learners. Moreover, real-life context and interactive tasks used in class foster more in-depth learning as well as greater student motivation and have increased learners’ confidence to produce in English. Thus, this study underlines CBI as an effective teaching method that equips learners with the language and the profession-relevant skills that are essential in the hospitality industry.